Performance Comparison of Wavelets Generated from Four Different Orthogonal Transforms for Watermarking With Various Attacks (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper proposes a watermarking technique using different orthogonal wavelet transforms like Hartley wavelet, Kekre wavelet, Slant wavelet and Real Fourier wavelet transform generated from corresponding orthogonal transform. These orthogonal wavelet transforms have been generated using different sizes of component orthogonal transform matrices. For example 256*256 size orthogonal wavelet transform can be generated using 128*128 and 2*2 size component orthogonal transform. It can also be generated using 64*64 and 4*4, 32*32 and 8*8, 16*16 and 16*16 size component orthogonal transform matrices. In this paper the focus is to compare the performance of above mentioned transforms generated using 128*128 and 2*2 size component orthogonal transform and 64*64 and 4*4 size component orthogonal transform in digital image watermarking. The other two combinations are not considered as their performance is comparatively not as good. Comparison shows that wavelet transforms generated using (128,2) combination of orthogonalÂ transform give better performances than wavelet transforms generated using (64,4) combination of orthogonal transformfor contrast stretching, cropping, Gaussian noise, histogram equalization and resizing attacks. Real Fourier wavelet and Slant wavelet prove to be better for histogram equalization and resizing attack respectively than DCT wavelet and Walsh wavelet based watermarking presented in previous work.